Creative Arts Therapy as a Potential Intervention to Prevent Burnout and Build Resilience in Health Care Professionals. (2020) - Reed, Katherine; Cochran, Kathryn L.; Edelblute, Anthony; Manzanares, Daniel; Sinn, Hillary; Henry, Michael; Moss, Marc
ABSTRACT : N/A: The delivery of health care is undergoing a rapid evolution that is dramatically changing the way health care professionals perform their job responsibilities. In this increasingly stressful work environment, professionals are experiencing alarming rates of burnout. Recent efforts to enhance wellness have been directed toward organizations. However, because of the nature of the work performed in intensive care units, interventions to develop individual resilience are also needed. Currently, medical centers are environments in which the emotional impact of work‐related trauma is often minimized and rarely processed. Some individuals may struggle to describe or express the impact of those traumas. Through nonverbal interventions, creative arts therapy can help people access, explore, and share authentic emotion in visual, musical, physical, or written form. By reconstructing meaning through transformative methods, participants may confront, reflect, and better cope with traumatic experiences while catalyzing social support networks and deepening relational bonds in the workplace.